PS1:3 Analysis of c9orf72 expansions in patients with systemic lupus erythematosus and rheumatoid arthritis: preliminary data. (21st March 2018) - Fredi, M; Biasiotto, G; Cavazzana, I; Filosto, M; Padovani, A; Franceschini, F; Zanella, I
Abstract : Background: The most frequent genetic cause of Amyotrophic Lateral Sclerosis (ALS) and Frontotemporal Lobar Dementia (FTLD) is a large hexanucleotide expansion (mostly hundred/thousand repeats) within a non-coding region of the C9orf72 gene. 1 The cut-off to distinguish normal and pathogenic expansions has not yet been defined, but most healthy individuals have 2–20 repeats. The pathogenic mechanism of the dominant mutation is most probably toxic gain of functions. Nonetheless, C9orf72 reduced expression has been observed in post-mortem brains of mutated patients. 2 Interestingly, while gene haploinsufficiency alone seems insufficient to cause neurodegeneration, decreased transcriptional activity with increasing numbers (>7) has been demonstrated in vitro 3 and knockout mice developped features of systemic lupus erythematosus (SLE). 4 We investigated C9orf72 gene in a cohort of patients with rheumatoid arthritis (RA) and SLE; as a control group we studied 49 ALS patients without pathogenic expansion. Methods: 29 SLE and 50 RA pts were screened, by the use of a PCR-based protocol, validated in our laboratory. 5 A cut-off of ≥9 repeat units was considered in our analysis. Results: No patients with large expansions were found. The average and median values of repeat units were 5.29 and 6 in SLE, 4.73 and 2 in RA and 4.8 and 5 in the control population. We individuated ≥9 repeat units in 5/30 (16.7%) SLE patients and 7/50 (14%) RA patients; a prevalence higher than ALS group (8.16%). We searched for clinical or serological differences among SLE pts with the normal and ≥9 repeat. Although those differences were not statistically significant, we reported a higher prevalence of kidney involvement in patients with a number of repeats ≥9 (5/6; 83.3% vs 7/23; 30.4%), p=0.056. Conclusion: Our preliminary results indicate that ≥9 repeats within the C9orf72 gene are detectable in a non negligible number of patients with systemic autoimmune disease, confirming the possible role of C9orf72 in autoimmune system. The possible association with specific subset of disease must be confirmed in a larger cohort of patients. References: . Neuron2011, 72:245–56. . Lancet Neurol2015, 14:291–301. . Mol Psychiatry2016, 21:1112–24. . Atanasio A, et al. Sci Rep2016;6:23204. . Mol Cell Probes2017;32:60–64.